2007
DOI: 10.1086/520730
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Laminar Growth in Morphologically Convergent Leaves and Flower Petals

Abstract: Distinct leaf laminar growth dynamics have been found previously in some filicalean ferns and angiosperm seed plants: a discrete zone of marginal growth versus diffuse intercalary growth throughout the leaf without a conspicuous marginal growth zone. The fern pinnules for which marginal growth is known are also morphologically distinct from dicots: one or two orders of dichotomizing veins ending only along the margin versus many orders that include internally directed veins and endings dispersed throughout the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…A similar observation was made, based on clonal analysis of leaf development, in cotton (Dolan and Poethig 1991 ). It has also been known for some time that while the lamina development in many ferns with marginally ending dichotomous veins depends on the marginal meristem, development of angiosperm leaves with many higher-order vein reticulations and internally directed, free-ending internal veinlets depends on dispersed, nonmarginal growth (Boyce 2007 ). In an unpublished work, one of the authors of this chapter, Krishnamurthy, has suggested that the marginal meristems of a developing leaf lamina are akin to the QC of RAM and SAM (see Chap.…”
Section: Post-initiation Developmentsupporting
confidence: 64%
See 1 more Smart Citation
“…A similar observation was made, based on clonal analysis of leaf development, in cotton (Dolan and Poethig 1991 ). It has also been known for some time that while the lamina development in many ferns with marginally ending dichotomous veins depends on the marginal meristem, development of angiosperm leaves with many higher-order vein reticulations and internally directed, free-ending internal veinlets depends on dispersed, nonmarginal growth (Boyce 2007 ). In an unpublished work, one of the authors of this chapter, Krishnamurthy, has suggested that the marginal meristems of a developing leaf lamina are akin to the QC of RAM and SAM (see Chap.…”
Section: Post-initiation Developmentsupporting
confidence: 64%
“…The most important function for these meristems is the determination of the basic number of laminal cell layers to be formed through characteristic planes of cell division. Although the concepts of marginal and submarginal meristems have been followed for a very long time to explain the morphogenesis of lamina (Boyce 2007 ), a number of investigators have indicated that the zone occupied by these meristems is not a site of elevated mitotic activity; these people have raised questions regarding its importance in lamina development. For instance, Merrill ( 1986a , b ) has emphasised that this zone may have a signifi cant role during the initiation of lamina but not during the later stages of lamina development.…”
Section: Post-initiation Developmentmentioning
confidence: 99%
“…Vascular plant leaves use internal airspaces regulated by stomata for gas exchange (Raven 1996;Boyce 2008a). Second, evidence from both living plants and the venation patterns of fossil leaves indicates that the ancestral form of tissue production in the growing leaves of all vascular plants was limited to discrete marginal zones of growth (Pray 1960;Zurakowski and Gifford 1988;Boyce and Knoll 2002;Boyce 2007). Other aspects of leaf organography, such as the evolution of differentiated abaxial/adaxial domains (see section on 'Proximal mechanisms underlying leaf shape diversity' below) and determinate leaf growth appear to arise independently in seed plants and other lineages, however, several of these lineages have co-opted the same underlying genetic pathways to regulate these developmental processes (see section on 'Proximal mechanisms underlying leaf shape diversity', Bharathan et al 2002;Harrison et al 2005;Sanders et al 2007;Tomescu 2009;Boyce 2010).…”
Section: A Brief History Of the Angiosperm Leaf And Shape Diversity Tmentioning
confidence: 99%
“…Whereas in ferns, leaf blade development depends on a marginal meristem (Boyce, 2007), its contribution in Arabidopsis is still under discussion (Donnelly et al, 1999;Tsukaya, 2013a). The different axes that determine the flat morphology of Arabidopsis leaves are formed early on (for a review: Tsukaya, 2013a).…”
Section: Phenotyping Leaf Development At a Cellular Levelmentioning
confidence: 99%